Kueski : Revolutionizing Consumer Credit in Mexico - Markovich, Sarit; Achwal, Nilima (London : Kellogg School of Management, 2017)
This case asks students to step into the role of Adalberto Flores, co-founder and CEO of Kueski, one of the first companies to develop a proprietary algorithm for online loan approval in Mexico. Mexico lacks a standardized credit scoring system, making it difficult for many Mexicans to get approved for a loan or credit card. This, together with the fact that Mexicans generally do not trust traditional banks, makes Mexico an attractive opportunity for fintech companies. Growth, however, could require fintech companies to partner with traditional banks. Students assume the role of Flores to think about the benefits and risks associated with a partnership between Kueski and traditional banks. Students are also challenged to compare the structure of U.S. financial services markets with the Mexican structure and consider the implications on the sustainability of fintech companies in the two markets. The teaching note analyzes the Mexican financial market and the benefits and threats it holds for fintech companies, and outlines a framework for evaluating the risk associated with partnerships.
Originally Published InMarkovich, S., & Achwal, N. (2017). Kueski: Revolutionizing consumer credit in Mexico. 5-117-005. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Flores, Adalberto; Consumer credit -- Mexico -- Case studies; Small business -- Mexico -- Case studies